Grain Size-Related Strengthening and Softening of a Precompressed and Heat-Treated Mg-Zn-Ca Alloy - Dobroň, Patrik; Drozdenko, Daria; Horváth Fekete, Klaudia; Olejňák, Juraj; Bohlen, Jan (Materials (Basel, Switzerland), 2020)
The impact of precompression, thermal treatment and its combination on the deformation behaviour of an extruded Mg-Zn-Ca (ZX10) alloy was studied with respect to a varied average grain size. The Hall-Petch plot was used to highlight the impact in a wide grain size interval. The initial texture of the wrought alloy was characterized by X-ray diffraction. Moreover, the evolution of microstructure and texture was provided by the electron backscatter diffraction (EBSD) technique. The obtained results indicate the strong contribution of deformation-thermal treatment on the resulting deformation behaviour. Particularly, after precompression and heat treatment, higher strengthening effect was observed in the reversed tensile loaded compared to compressed samples without any change in the Hall-Petch slope throughout the grain size interval. Unlike this strengthening effect, a reversed tension-compression yield asymmetry with higher strength values in compression has been obtained.
Keywords: deformation-thermal treatment; Hall–Petch relationship; yield asymmetry; Mg alloy